2022
DOI: 10.1021/acs.analchem.2c01047
|View full text |Cite
|
Sign up to set email alerts
|

Second-Derivative-Based Background Drift Removal for a Tonic Dopamine Measurement in Fast-Scan Cyclic Voltammetry

Abstract: The dysregulation of dopamine, a neuromodulator, is associated with a broad spectrum of brain disorders, including Parkinson's disease, addiction, and schizophrenia. Quantitative measurements of dopamine are essential for understanding dopamine functional dynamics. Fast-scan cyclic voltammetry (FSCV) is the most widely used electrochemical technique for measuring real-time in vivo dopamine level changes. Standard FSCV has only been used to analyze "phasic dopamine" (changes in seconds), because the gradual gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Thus, the tonic DA level remains unaffected by background drift accumulation over repeated scans (blue arrow) ( Figure 1F ). In the previous study, we confirmed sensitivity and selectivity of the advanced FSCV technique with SDBR in vitro ( Kang et al, 2022 ). Regarding the sensitivity of its method, we analyzed calibration plot against various dopamine concentrations (62.5–1,000 nM).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Thus, the tonic DA level remains unaffected by background drift accumulation over repeated scans (blue arrow) ( Figure 1F ). In the previous study, we confirmed sensitivity and selectivity of the advanced FSCV technique with SDBR in vitro ( Kang et al, 2022 ). Regarding the sensitivity of its method, we analyzed calibration plot against various dopamine concentrations (62.5–1,000 nM).…”
Section: Resultssupporting
confidence: 77%
“…However, continuous FSCV amplifies noise signals, notably from chemical adsorption on the surface of the carbon probe, which poses challenges in signal detection. In the previous study, we developed an FSCV technique used in conjunction with the SDBR method and examined the DA selectivity and sensitivity of the technique in vitro and in vivo ( Kang et al, 2022 ). In the current study, while building upon our prior findings, we have extended the application of this technique for in vivo pharmacodynamic analysis of levodopa-induced dyskinesia (LID) in the PD model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Real-time monitoring of DA levels in the brain is crucial, and various techniques have been developed to achieve this, ranging from microdialysis to fast-scan cyclic voltammetry (FSCV) techniques, using different types of neural probes. [10][11][12] While various types of probes have been proven to be useful tools for studying DA dynamics in the brain, they often suffer from drawbacks associated with the use of rigid materials. [13][14][15] One of the most significant drawbacks is the potential for undesirable tissue damage caused by the mechanical mismatch between the rigid probe and the soft tissues of the brain.…”
Section: Introductionmentioning
confidence: 99%